ANALISIS TRANSAKSI JUAL BELI PRODUK SMART HAFIZ PRESPEKTIF FIQIH MUAMALAH (STUDI KASUS PADA PT. TIGARAKSA SATRIA BLOKAGUNG BANYUWANGI) - Mira Ustanti; Wulan Alif Qurani (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
The objectives of this research are: 1) To analyze buying and selling transactions for Smart Hafiz products at PT. Tigaraksa Satria Blokagung Banyuwangi. 2) To analyze buying and selling transactions for smart Hafiz products from the perspective of muamalah fiqh at PT. Tigaraksa Satria Blokagung Banyuwangi muamalah fiqh perspective. This research uses a qualitative research method with a case study approach. The results of this research are 1) practice of buying and selling transactions for smart Hafiz products at PT. Tigaraksa Satria uses the following system: First, cash by direct payment and filling in the buyer data form clearly and validly. Second, installments with payment within a period of 5 months provided that the buyer is someone who is known and can be trusted. Third, social gathering, namely buyers are allowed to choose to participate in social gathering according to their wishes for 3, 5 or 10 months. 2) The system used in buying and selling transactions for Smart Hafiz products at PT. Tigaraksa Satria falls under the criteria of a bai’ or sale and purchase contract, a muajjal/Bai’ Bitsaman Ajil contract, a qardh (debt) contract according to the perspective of muamalah fiqh.